2018
DOI: 10.1136/gutjnl-2017-315783
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical validation of the Genedrive point-of-care test for qualitative detection of hepatitis C virus

Abstract: ObjectiveRecently approved direct acting antivirals provide transformative therapies for chronic hepatitis C virus (HCV) infection. The major clinical challenge remains to identify the undiagnosed patients worldwide, many of whom live in low-income and middle-income countries, where access to nucleic acid testing remains limited. The aim of this study was to develop and validate a point-of-care (PoC) assay for the qualitative detection of HCV RNA.DesignWe developed a PoC assay for the qualitative detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…Currently, two CE-in vitro diagnostic point-of-care platforms (Genedrive ® ) and Xpert ® (Cepheid) for HCV RNA NAT in plasma exist, with one (Xpert ® ) receiving WHO prequalification in 2017. 8,9 However, with the existing point-of-care tests there still remains the issue of plasma separation. Whole blood samples of 50-70 µL have been demonstrated as an alternative method to decentralise and simplify sample collection using dried blood spots (DBS).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, two CE-in vitro diagnostic point-of-care platforms (Genedrive ® ) and Xpert ® (Cepheid) for HCV RNA NAT in plasma exist, with one (Xpert ® ) receiving WHO prequalification in 2017. 8,9 However, with the existing point-of-care tests there still remains the issue of plasma separation. Whole blood samples of 50-70 µL have been demonstrated as an alternative method to decentralise and simplify sample collection using dried blood spots (DBS).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…One of the novel solutions to mitigate the dependence on skilled laboratories and personnel is the emergence of simple point‐of‐care tests for HCV RNA. Currently, two CE‐in vitro diagnostic point‐of‐care platforms (Genedrive ® ) and Xpert ® (Cepheid) for HCV RNA NAT in plasma exist, with one (Xpert ® ) receiving WHO prequalification in 2017 …”
Section: Introductionmentioning
confidence: 99%
“…Patient follow‐up and linkage to care must also be organized because previously diagnosed patients may be lost to follow‐up in the presence of treatment restrictions (prioritization) . This requires new technologies such as RDOT or ‘Point of Care’ tests, which allow a serological diagnosis, and especially detection of positive viraemia within 20‐30 minutes, for a ‘test and treat’ policy . All these measures can help meet the challenge by improving ‘diagnostic burn‐out’, with five times more viral C infections than diagnosed in 2016 and five times fewer cures than new infections …”
Section: Improving Screening Of Hcv Infectionmentioning
confidence: 99%
“…The work conducted by Llibre et al 3 paves the way for further innovations and strategies for the reduction of the HCV epidemic.…”
mentioning
confidence: 99%
“…From a large case–control study including samples from HCV-infected -treatment naïve- and uninfected patients identified in 2 European (France and UK) and 10 African countries, the authors assessed the performance of the new test for the detection of HCV RNA using the Abbott real-time PCR assay as a reference 3. They found high diagnostic sensitivity and specificity of the assay (close to 100%) to detect HCV RNA in Western as well as South-African laboratories with pangenotypic performance.…”
mentioning
confidence: 99%